Pengaruh posisi tindakan suction terhadap perubahan saturasi oksigen pada pasien yang terpasang ventilasi mekanik di Ruang Intensive Care Unit (ICU) - Popy Irawati; Fitri Apriana; Roswita Hasan (STIKes Surya Global Yogyakarta, 2021)
One of the conditions that cause respiratory failure is airway obstruction. Including obstruction of the Endotracheal Tube (ETT). Endotracheal Tube (ETT) that has been installed requires special attention in maintaining the cleanliness of the accumulation of secretions. Therefore, it is necessary to suction mucus (suction) which aims to maintain a patent airway due to accumulation of secretions. The purpose of this study is to analyze the effect of the suction position on changes in oxygen saturation in mechanically ventilated patients. This type of research is a quasi-experimental research design with one group pre-post test design. The sample technique used by the researcher is a total sampling technique with a total sample of 20 respondents. The respondents of this study were patients in the ICU who received suction. The action taken is the provision of a semi-Fowler position and a supine position when suction is performed. The statistical test used is the dependent t test. The average SpO2 before suction in the semi-Fowler position was 97.10 and after that it was 90.50. The average SpO2 before suction in the supine position was 97.75 and after that it was 85.30. The results of the comparison test between before and after the intervention obtained a p value of 0.000 (p value 0.05). The conclusion of this study is that there is an effect of the semi-Fowler suction position and the supine/supine position on oxygen saturation in patients who are mechanically ventilated.